International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.1990.115971
|View full text |Cite
|
Sign up to set email alerts
|

Environmental robustness in automatic speech recognition

Abstract: This dissertation describes a number of algorithms developed to increase the robustness of automatic speech recognition systems with respect to changes in the environment. These algorithms attempt to improve the recognition accuracy of speech recognition systems when they are trained and tested in different acoustical environments, and when a desk-top microphone (rather than a close-talking microphone) is used for speech input. Without such processing, mismatches between training and testing conditions produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
4

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(82 citation statements)
references
References 10 publications
0
78
0
4
Order By: Relevance
“…In the conventional approach, sound is listened by a single process which gives it to the SR engine for comparison on the basis of static grammar [2] loaded before the execution of SR system. The listener finds the probability of the recognized word and gives the result on the basis of more probability in single attempt.…”
Section: Related Workmentioning
confidence: 99%
“…In the conventional approach, sound is listened by a single process which gives it to the SR engine for comparison on the basis of static grammar [2] loaded before the execution of SR system. The listener finds the probability of the recognized word and gives the result on the basis of more probability in single attempt.…”
Section: Related Workmentioning
confidence: 99%
“…The CMU SPHINX-I speech recognizer [10] was trained using speech recorded in an office environment using the speakerindependent alphanumeric census database [1] with the omnidirectional desktop Crown PZM6FS microphone. Identical samples of 1018 training utterances from this database from 74 speakers were presented to the inputs of the multi-microphone system described in Figure 1.…”
Section: Effects Of Cross-correlation Processing On Speech Recognitiomentioning
confidence: 99%
“…Results of several studies have demonstrated that even automatic speech recognition systems that are designed to be speaker independent can perform very poorly when they are tested using a different type of microphone or acoustical environment from the one with which they were trained, even in a relatively quiet office environment (e.g. [1]). Applications such as speech recognition over telephones, in automobiles, on a factory floor, or outdoors demand an even greater degree of environmental robustness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, introducing a new type of feature [1,2] or applying a feature normalization algorithm [3][4][5][6][7] requires retraining of the acoustic model. Acoustic model adaptation [8,9] can be used only when one has access to the detailed structure of the acoustic model.…”
Section: Introductionmentioning
confidence: 99%